Donnie Brasco [videorecording (Blu-Ray + DVD)] - Newell, Mike, 1942-; Pacino, Al, 1940-; Depp, Johnny; Madsen, Michael; Pistone, Joseph D. (Mill Creek Entertainment, 2019)
A dramatized account of Joseph D. Pistone's experiences as an undercover FBI agent who successfully infiltrated the dangerous world of the mafia in the 1970s and how his personal feelings almost led to his death.